THE APPLICATION OF HOMBO BATU LOCAL WISDOM-BASED LEARNING IN ENHANCING STUDENT DISCIPLINE AND COOPERATION IN THE NIAS ISLANDS - Harefa, Darmawan (LPPM Universitas Nias Raya, 2025)
This study aims to analyze the implementation of Hombo Batu local wisdom-based learning in improving student discipline and cooperation in the Nias Islands. Hombo Batu is a local cultural tradition that contains values of cooperation, discipline, and responsibility, which are integrated into learning activities in schools to strengthen students' character. This research employs a qualitative approach with a case study design conducted in several primary and secondary schools in the Nias Islands. Data were collected through observation, interviews, and document analysis related to the implementation of Hombo Batu activities in the learning process. The results show that the application of Hombo Batu-based learning is effective in improving student discipline, as reflected in time management, responsibility for tasks, and adherence to rules. Additionally, student cooperation also increased, demonstrated by better collaboration in group tasks and joint activities. This learning approach also had a positive impact on strengthening students' local cultural identity. This study suggests that local wisdom-based learning, such as Hombo Batu, should be further expanded and integrated into the educational curriculum in other regions, with attention to infrastructure and teacher training.